Quantifying water-related ecosystem services potential of the Kangchenjunga Landscape in the eastern Himalaya: a modeling approach - Manish Shrestha; Santosh Nepal (Hydrology Research, 2022)
Quantifying water-related ecosystem services (WES) helps to secure limited and valuable water resources sustainably. Mainstreaming these ecosystem services into policy and decision-making requires accurate information at the local level. This paper aims to quantify provisioning and regulating freshwater ecosystem services potential in the Kangchenjunga Landscape using a hydro-ecological model. This study is the first to use the J2000 hydrological model to estimate annual and seasonal WES. The model output was validated against snow-cover and river discharge, after conducting a sensitivity analysis of the input parameter. High precipitation and low evapotranspiration resulted in rich water availability in the landscape. It was found that the precipitation amount in the landscape is highly seasonal, resulting in high variation in water availability. Snowfall, accounting for 4% of the total precipitation still plays an important role in regulating water resources. Nearly 100% of the discharge during the dry period originates from groundwater and melt runoff. This study highlights the importance of the presence of snow and glacier to sustain the ecosystem in the landscape. This model-derived information could further be used for decision-making and evaluating the impact of climatic and land use changes. HIGHLIGHTS The study quantified WES potential in the Kangchenjunga Landscape.; The J2000 model provided important insight into the hydrological dynamics at the landscape level.; Potential provisioning and regulating ecosystem services are quantified.; Snow plays a vital role in maintaining ecosystem services in the landscape.;